EFFECT OF AQUEOUS CRUDE EXTRACT OF TIGER NUT (CYPERUS ESCULENTUS) ON PENILE ERECTION-RELATED BIOCHEMICAL PARAMETERS IN MALE WISTAR RATS - Ubi, Ubi Ebri; Osibemhe, Martin; Omaji, Gloria Onyimowo (FUDMA Journal of Sciences, 2025)
There is an increase in the cases of erectile dysfunction and the remedies so far are not without side effects thus, this study is aimed at investigating the influence of aqueous crude extract of tiger nut (Cyperus esculentus) on some important biochemical indices involved in penile erection in male Wistar albino rats. Twenty-four adult male Wistar rats were divided into four (4) groups of five (5) rats each. One group (control) received distilled water, the other groups received 250, 500 and 1000 mg/kg of C. esculentus aqueous crude extract respectively for fourteen (14) days. Administration was done orally (once daily) with the aid of a gavage. At the end of the experimental period, blood samples were collected through the abdominal aorta into plain sample containers to obtain serum for biochemical analysis. Nitric oxide (NO), sex hormones, fasting blood glucose, lipid profile, serum liver enzymes (ALT and AST) and haematological parameters were assayed using standard methods. Body weight of the animals and organs (testis and kidney) were also monitored at intervals of seven (7) days after basal value had been taken. The results showed significant (p
Keywords: Tiger nut; Testosterone; Testes; Nitric oxide; Kidney